Mechanistic study of leukopenia treatment by Qijiao shengbai Capsule via the Bcl2/Bax/CASAPSE3 pathway - Jiang, Siyue; Wang, Pengjiao; Sun, Xiaodong; Zhang, Min; Zhang, Shuo; Cao, Yu; Wang, Yuben; Liu, Li; Gao, Xiuli (Frontiers in Pharmacology, 2024)
Chemotherapy can cause leukopenia, which can affect bone marrow function and impact the effectiveness of cancer treatment. This study aimed to investigate the bioactive components of Qijiao Shengbai Capsule (QJSB) and its potential targets for treating leukopenia using network pharmacology and validation experiments. The study first analyzed the components of QJSB using UPLC-Q-Exactive. The efficacy of QJSB was then studied using a leukopenia mouse model induced by cyclophosphamide (CTX) and a multi-omics approach. The study identified 16 key components of QJSB that increased leukocyte count in leukopenic mice. Network pharmacology and multi-omics analysis revealed that the PI3K-Akt and MAPK signaling pathways are important in treating leukopenia with QJSB. Five specific targets (JUN, FOS, BCl2, CASPAS3) were identified, and molecular docking showed that Sophoridine and Daidzein bind well to these targets. Validation experiments confirmed that QJSB can regulate genes related to apoptosis and inhibit apoptosis, suggesting that apoptosis may play a key role in the development of leukopenia. QJSB was also found to increase the number of CD4 + T cells in leukopenic mice, indicating its potential to improve immune function.